Barriers and Facilitators of Pediatric Weight Management Among Diverse Families. (June 2015) - Brown, Lauren; Dolisca, Sarah-Bianca; Cheng, Jennifer K.
Objective . To describe barriers and facilitators relevant to pediatric weight management from the perspective of at-risk overweight children and families. Methods . Systematic thematic analysis of semistructured interviews with overweight children and families from diverse backgrounds at a large, urban academic pediatrics practice. Results . Twenty-five parents and their children ages 2 to 18 years with mean body mass index percentile of 96th% (standard deviation 4.3) participated. Fifty-six percent were Black; 40% were Hispanic/Other race. Perceived barriers to successful weight management included ( a ) inadequate resources (financial, time, access to programming, knowledge), ( b ) challenging social contexts (cultural practices and expectations, interpersonal dynamics), ( c ) negative emotional state (lack of confidence, defeat, loneliness), and ( d ) denial. Participants described linkages to resources, child–parent—provider partnerships, and consistent support as key elements in successful weight management. Participants also endorsed technology use for weight management support. Conclusions . Multiple barriers and facilitators affect weight management among at-risk families, which should be considered in future obesity interventions.